Organizational and Methodological Issues of Organizing Audit of Fixed Assets in Accordance with International Standards - Khusanovich, Turaboev Temurbek; Shaniyazov, Sh. Sh. (Research Parks Publishers, 2023)
This article aims to explore the organizational and methodological challenges involved in conducting audits of fixed assets in compliance with international standards. The audit of fixed assets plays a crucial role in providing assurance on the accuracy and reliability of financial statements. However, ensuring compliance with international standards requires careful planning and adherence to established methodologies. This article presents a comprehensive overview of the key organizational and methodological considerations, including tables and frameworks, for effectively conducting audits of fixed assets.